The anticancer compound identification from chloroform extract of Rhizopora mucronata stem bark - Diastuti, Hartiwi; ., Warsinah (Indonesian Journal of Pharmacy, 2010)
Previous  reasearch  reported  that  chloroform  extract  that  was  partitioned from etanol exctracts  of  R. mucronata  stem bark had sitotoxic against Myeloma cells  (Diastuti,  2008).  This  research  was  aimed  to  fractinate  the  chloroform extract  of  R.  mucronata  stem  bark  and  cytotoxicity  test  againts  Myeloma  cells, then  identification  the  cytotoxic  compounds.  The  ethanol  extracts  of R.  mucronata  steam  bark  was  partitioned  with  chloroform.  The  chloroform extracts was fractinated by coloum chromatography with gradient eluent were nhexane, chloroform, etilacetate  and methanol respectivelly. Cytotoxicity test the fraction  of  chloroform  extracts  were  conducted  on  Myeloma  cells  by  MTT methods.  Identification   the  compoud  of  fraction  that  had  a  highest  cytotoxic againts  Myeloma  cells  conducted  using  IR  spectrometer,  and  GCMS.  The  result showed  that  2b  fraction  of   R.  mucronata  stem  bark  had  a  highest  cytotoxic againts  Myeloma  cells,  having  IC50  equal  to  5.122   µg/mL.  Identification  of chemical compounds  showed that 2b fraction  contained two steroid compounds were 4 methyl- colest-24-en-3-ol and 4-methyl-stigmast-22-en-3-ol.Key words : R. Mucronata, anticancer, Myeloma cells, steroids